Identification of microRNA biomarkers simultaneously expressed in circulating extracellular vesicles and atherosclerotic plaques - Brandes, Florian; Meidert, Agnes S.; Kirchner, Benedikt; Yu, Mia; Gebhardt, Sonja; Steinlein, Ortrud K.; Dolch, Michael E.; Rantner, Barbara; Tsilimparis, Nikolaos; Schelling, Gustav; Pfaffl, Michael W.; Reithmair, Marlene (Frontiers in Cardiovascular Medicine, 2024)
Background. Atherosclerosis is a widespread disorder of the cardiovascular system. The early detection of plaque by circulating biomarkers is highly clinically relevant to avoid major complications such as stroke or heart attacks. It is known that extracellular vesicles (EVs) are important in intercellular communication in atherosclerotic disorders and carry many components of their cells of origin including microRNAs (miRNAs). In this study, we tested the assumption that miRNAs present in material acquired from plaques in patients undergoing surgery for atherosclerotic carotid artery stenosis are also expressed in circulating EVs obtained from the identical patients. This would allow a liquid biopsy approach for the detection of plaques. Methods. We studied 22 surgical patients with atherosclerotic carotid arterial stenosis and 28 controls. EVs were isolated from serum by precipitation. miRNA expression profiles of serum-derived EVs were obtained by small RNA sequencing and in plaque material simultaneously acquired from patients. A comparative analysis was performed to identify circulating atherosclerosis-associated miRNAs that are also detectable in plaques. Results. Seven miRNAs were found to be differentially regulated in patient serum compared to healthy controls. Of these, miR-193b-5p, miR-193a-5p and miR-125a-3p were significantly upregulated in patients compared to controls and present circulating EVs and plaque material. Over representation analysis of experimentally validated mRNA targets revealed increased regulation of inflammation and vascular growth factors, key players in atherosclerosis. Conclusion. Our findings suggest that circulating EVs reflect plaque development in patients with symptomatic carotid artery stenosis which can serve as biomarker candidates for the presence of atherosclerotic plaques.